Process simulation using WITNESS - Al-Aomar, Raid (John Wiley & Sons, Inc., 2015)
"The first book to cover simulation using the popular software WITNESS, Process Simulation Using WITNESS helps professionals understand the theory behind simulation in a simple and practical manner while learning how to build simulation models with the software. This book outlines the role of simulation in contemporary initiatives for lean systems design and operations as well as Six Sigma applications. Emphasizing real-world applications of simulation modeling in both services and manufacturing sectors, the book is suitable for a broad audience, including system, simulation, material handling, layout, and operations engineers"- Resumé vydavatel
Keywords: Witness (software); stochastické procesy; počítačová simulace; operační výzkum; zpracování dat; průmyslové inženýrství; grafické metody; stochastic processes; computer simulation; operations research; data processing; production engineering; graphical methods; elektronické knihy; monografie; electronic books; monographs